IMPAK KECERDASAN EMOSI DALAM KALANGAN GURU PENDIDIKAN ISLAM KESAN PELAKSANAAN PERINTAH KAWALAN PERGERAKAN: IMPACT OF EMOTIONAL INTELLIGENCE AMONG ISLAMIC EDUCATION TEACHERS BY THE IMPLEMENTATION OF MOVEMENT CONTROL ORDER - Othman, Mohd Syaubari; Mohd Jamil, Mohd Ridhuan (Journal of Islamic Educational Research, 2021)
This study aims to identify the impact of emotional intelligence among teachers in Manjung District the impact of the implementation of movement control orders (MCO). This study involved IET who teach in Manjung District in both primary and secondary schools. The impact of the implementation of PKP is examined from four indicators, namely the use of computer literacy, online teaching, limited internet access and student readiness. These indicators are analysed and linked to the four elements of teachers’ emotional intelligence, namely Self -Awareness. Self -Control, Self -Motivation, Empathy and Social Skills. This study uses descriptive analysis. All these data collection instruments were constructed by the researcher with modifications from the instruments from previous studies and their contents were validated by an expert reference panel. The level of Cronbach’s alpha reliability value obtained is high that is between (0.82173). A total of 171 teachers were selected at simple random to answer the prescribed questionnaire instruments. Overall, the results of the study found that the impact of IET emotional intelligence based on the implementation of PKP is at a moderate level based on the findings and analysis of the questionnaire obtained. The implications and recommendations put forward place a need for ministries, schools, teachers, and the community to enhance the level of understanding of emotional management to the IET in relation to the impact on the implementation of PKP in ensuring the teaching and learning process is implemented effectively.